Optimizing Electrolyte Additive Loadings in NMC532/Graphite Cells: Vinylene Carbonate and Ethylene Sulfate. Issue 1 (11th January 2021) - Taskovic, T.; Thompson, L. M.; Eldesoky, A.; Lumsden, M. D.; Dahn, J. R.
Abstract : A matrix of LiNi0.5 Mn0.3 Co0.2 O2 /graphite cells filled with 1.33 molal LiPF6 in EC:EMC:DMC (ethylene carbonate: ethyl methyl carbonate: dimethyl carbonate) (25:5:70 by volume) electrolyte and different weight percentages of vinylene carbonate (VC) and ethylene sulfate (DTD) electrolyte additives underwent prolonged charge-discharge cycling at 20 °C and 40 °C. The volume of gas produced during formation and cycle testing was measured. The impedance spectra of the cells before and after cycling was measured. After testing, the electrolyte was extracted for study by nuclear magnetic resonance spectroscopy (NMR) and gas chromatography/mass spectroscopy (GC-MS) to determine what changes in electrolyte composition had occurred. Some cells had their negative electrodes studied by scanning micro-X-ray fluorescence to quantify the amount of transition metals that transferred from the positive electrode to the negative electrode during the testing. Cells containing 1% VC or 2% VC with an additional 1% DTD by weight had the best capacity retention and lowest impedance growth. NMR and GC-MS suggest that these additive combinations promote increased electrolyte salt consumption which may represent a source of lithium to replenish the lithium inventory. Only a small amount of transition metals (0.03% or less) originating from the positive electrode active material was found on the negative electrode after testing. Most cells had over 1500 cycles at both 20 °C and 40 °C conditions.